EXTRAÇÃO DE ÓLEO DE FARELO DE ARROZ UTILIZANDO CO2 SUPERCRÍTICO - LAURA FONTANA LIKES , ANA; DO NASCIMENTO VIEIRA , GABRIELA; AUGUSTA BONIATTI LIBARDONI , MARIA; ROSSI ABAIDE , EDERSON; L. ZABOT , GIOVANI; V. TRES , MARCUS (Salão do Conhecimento, 2020)
Projeto de Iniciação Científica